Forum: Thinking Theoretically in Unsettled Times: COVID-19 and Beyond. Issue 3 (10th May 2021) - Sterling-Folker, Jennifer; Freyberg-Inan, Annette; Wilcox, Lauren; Ozguc, Umut; Shinko, Rosemary E
Abstract: This collection of essays seeks to theorize the politics of the COVID-19 pandemic in international relations (IR). The contributions are driven by questions such as: How can theorizing help us understand these unsettled times? What kind of crisis is this? What shapes its politics? What remains the same and what has been unsettled or unsettling? In addressing such questions, each of the participants considers what we may already know about the pandemic as well as what might be ignored or missed. Collectively, the forum pushes at the interdisciplinary boundaries of IR theorizing itself and, in so doing, the participants hope to engender meaningful understandings of a world in crisis and encourage expansive ways of thinking about the times that lie beyond.